2022
DOI: 10.3389/fcvm.2022.844312
|View full text |Cite
|
Sign up to set email alerts
|

Association of Left Ventricular Diastolic Dysfunction With Cardiovascular Outcomes in Patients With Pre-dialysis Chronic Kidney Disease: Findings From KNOW-CKD Study

Abstract: BackgroundThe impact of left ventricular diastolic dysfunction (LVDD) on cardiovascular (CV) outcomes in patients with pre-dialysis chronic kidney disease (CKD) has been rarely unveiled. We here investigated the association of LVDD with CV outcomes and all-cause mortality in patients with pre-dialysis CKD.MethodsA total of 2,135 patients with pre-dialysis CKD from the Korean Cohort Study for Outcomes in Patients With Chronic Kidney Disease (KNOW-CKD) cohort were dichotomized by the absence or presence of LVDD,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…In patients with aortic valve stenosis, LVEF were significantly lower than that of patients with normal aortic valve ( 60 ). Left ventricular diastolic dysfunction was another predictor for all-cause mortality and cardiovascular outcomes in pre-dialysis CKD patients, while a stringent linear correlation was also clarified between E / e ratio and mortality ( 61 ). Our study corroborates the notion that several echocardiography parameters could be a marker of CVC in CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with aortic valve stenosis, LVEF were significantly lower than that of patients with normal aortic valve ( 60 ). Left ventricular diastolic dysfunction was another predictor for all-cause mortality and cardiovascular outcomes in pre-dialysis CKD patients, while a stringent linear correlation was also clarified between E / e ratio and mortality ( 61 ). Our study corroborates the notion that several echocardiography parameters could be a marker of CVC in CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In Shu's KNOW-CKD study, LVDD was independently associated with adverse CV outcomes and all-cause mortality in patients with predialysis CKD [51]. Liang et al proved that systolic dysfunction and LVDD demonstrated mutually augmentative effects on CV mortality and suggested that, along with traditional nephroprotection, early cardioprotection should be given priority in CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic information was collected from all eligible participants, as previously described ( 20 ). The methods for anthropometric measures, such as height, weight, waist circumference (WC), body mass index (BMI), and systolic and diastolic blood pressures (SBP and DBP), are also previously described ( 21 ). Venous samples were collected following overnight fasting, to determine hemoglobin, creatinine (Cr), TG, HDL-C, LDL-C, total cholesterol, fasting glucose, high-sensitivity C-reactive protein (hs-CRP), albumin, and 25-hydroxyvitamin D [25(OH) vitamin D] levels at the baseline.…”
Section: Methodsmentioning
confidence: 99%